Role of H4 receptor in histamine-mediated responses in human melanoma - Massari, Noelia Andrea (2011)
We have previously reported that histamine at micromolar concentrations reduces the proliferation of melanoma cell lines. It is also known that melanoma cells express histamine H1, H2 and H3 receptors. The aim of this work was to investigate the presence of histamine H4 receptor (H4R) in human melanoma cells and its associated biological processes. In order to better understand the importance of histamine in tumor development, we explored the expression of H4R in human melanoma tissue biopsies. The expression of H4R in WM35 and M1/15 cells was analyzed by RT-PCR, Western blot and immunocytochemistry. To characterize the biological responses we evaluated cell proliferation by clonogenic assay and BrdU incorporation. In addition, cell senescence and differentiation were determined by β-galactosidase enzyme assay and dopa oxidase activity, respectively. The expression levels of H4R were determined by immunohistochemistry in 19 samples of human malignant lesions. Results indicate that melanoma cells express H4R at the mRNA and protein level. By using histamine agonists, antagonists and H4 siRNA we showed that the inhibitory effect of histamine on proliferation was in part mediated through the stimulation of the H4R. The decrease in proliferation was associated with an induction of cell senescence and an increase in melanogenesis that is a differentiation marker of these cells. Furthermore, H4R was expressed in 42% of human melanoma biopses. To our knowledge this is the first report that describes the presence of the H4R in melanoma cells and tissue suggesting a potential therapeutic application of H4R ligands.